Application of phenol-cresol-formaldehyde resin as an adhesion promoter for bitumen and asphalt concrete. Issue 12 (2nd December 2021) - Gunka, Volodymyr; Demchuk, Yuriy; Sidun, Iurii; Miroshnichenko, Denis; Nyakuma, Bemgba B.; Pyshyev, Serhiy
Abstract : In this study, the phenol-cresol-formaldehyde (PhCR-F) resin was synthesised from the phenolic fraction of coal tar resin and formaldehyde through polycondensation. The physico-mechanical properties of the asphalt concrete were subsequently characterised to examine its water saturation, coefficient of long-term water-resistance (after 15 and 30 days), and compressive strength (at 20°C and 50°C). The results revealed that the addition of PhCR-F markedly increased the adhesion index with the surface of granite aggregates and glass before and after heating the bitumen. Furthermore, the PhCR-F addition enhanced the bitumen softening point, long-term water resistance, and thermo-stability but decreased the water-saturation index along with the penetration and ductility of bitumen. In conclusion, the study findings revealed that the synthesised PhCR-F resin is a promising adhesion promoter in pavement grade oil bitumen for application with asphalt concrete.